(untitled) (Research, Society and Development, 2022)
The objective of this work was to analyze the severity of burned areas in the municipality of Poconé located in the State of Mato Grosso. Remote sensing techniques were used, using the OLI sensor (Operational Land Imager) of the Landsat 8 satellite to analyze the severity levels with 3 scenes in April (pre-fire) and 3 scenes in September (post-fire) The dNBR (Normalized Burn Ratio Difference) allowed the identification of 70,08% of burned areas in the total area of the municipality, reaching about 1.201.269,36 hectares. The areas affected by fires in the present biomes were also analyzed in the municipality , computing about 68,80% in the Cerrado biome and 70,41% in the Pantanal Biome, totaling an area of 228.947,09 ha and 972.038,65 ha, respectively.